Nurses' knowledge and practice toward computed tomography safety protocols - Maaidah Algamdi; Ali Alghamdi; Khawla Dauod; Khaleda Alatawi; Manar Alrawaili; Mawaddah Alhwiti; Ablah Albalawi (Universidade Federal do Ceará, 2022)
Objective: to assess nurses' knowledge and practice toward computed tomography scan safety guidelines. Methods: a cross-sectional study was conducted using a convenience sample of 131 nurses from two government hospitals. Self-designed questionnaire was used to assess nurses' sociodemographic characteristics, knowledge, and practice. Descriptive analysis was performed to evaluate characteristics, correlations were evaluated using Spearman's rank correlation coefficient, and the Mann-Whitney U and the Kruskal-Wallis H tests were used to compare the mean ranks of knowledge and practice scores. Results: most respondents were female (91.6%), were aged 20-29 years (57.3%), and had bachelor's degrees (74%). Knowledge and practice levels were 58% and 78.9% respectively. A positive correlation between knowledge and practice was observed among nurses (r=0.684, p<0.001). No statistically significant differences were observed between sociodemographic characteristics and knowledge and practice scores. Conclusion: nurses showed adequate level of practice toward computed tomography scan safety preparations while their knowledge level was deficient. Contributions to practice: this study informs the importance of knowledge in guiding nursing practice toward appropriate computed tomography scan safety measures.